2023
DOI: 10.3390/ijms24033007
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of R. pulmo Jellyfish-Collagen-Coated Well Plates for Cytocompatibility Analyses of Biomaterials

Abstract: Cytocompatibility analyses of new implant materials or biomaterials are not only prescribed by the Medical Device Regulation (MDR), as defined in the DIN ISO Norm 10993-5 and -12, but are also increasingly replacing animal testing. In this context, jellyfish collagen has already been established as an alternative to mammalian collagen in different cell culture conditions, but a lack of knowledge exists about its applicability for cytocompatibility analyses of biomaterials. Thus, the present study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The study showed the positive effect of dead jellyfish mass on the rheological characteristics of the mixture, namely on mobility, as well as on the mechanical characteristics of hardened concrete. This study, as well as previously known research considering the use of dead jellyfish mass in other sectors of the economy [16][17][18][19], provided impetus for additional research to study the effect of using Black Sea dead jellyfish as a plasticizing additive in cement composites and the development of existing ideas about the structure formation and properties of concrete using dead jellyfish mass.…”
Section: Introductionmentioning
confidence: 73%
“…The study showed the positive effect of dead jellyfish mass on the rheological characteristics of the mixture, namely on mobility, as well as on the mechanical characteristics of hardened concrete. This study, as well as previously known research considering the use of dead jellyfish mass in other sectors of the economy [16][17][18][19], provided impetus for additional research to study the effect of using Black Sea dead jellyfish as a plasticizing additive in cement composites and the development of existing ideas about the structure formation and properties of concrete using dead jellyfish mass.…”
Section: Introductionmentioning
confidence: 73%
“…To evaluate the cytocompatibility of the BBS combined with 18 coatings based on the bioactive cations strontium (Sr 2+ ) and magnesium (Mg 2+ ) as well as PLGA coating, XTT cell viability assays were conducted using L929-fibroblasts and Normal Human Osteoblasts (NHOsts) following the DIN ISO 10993-5 protocol as previously described ( Gogele et al, 2020 ; Schroepfer et al, 2020 ; Pantermehl et al, 2022 ; Ren et al, 2023 ). Based on the cytocompatibility analyses, the material types with a viability above 70% compared to the negative control group as defined within the DIN ISO norm were considered cytocompatible and used for further material characterizations and in vivo studies.…”
Section: Resultsmentioning
confidence: 99%